Dental Bleaching: 'Now I can Smile for my Selfies' – Paediatric Patients' Perspectives. Issue 4 (December 2021) - Ilyas, Nabeel; Marshall, Sophie; Ahluwalia, Meera
Children presenting with discoloured teeth commonly suffer from low self-esteem. This paper reports the findings from a questionnaire evaluating changes brought about by dental bleaching and the psychosocial effects of bleaching on 22 patients. All patients reported to like the overall appearance of their teeth following bleaching and reported a significant improvement in mental wellbeing. In the current climate where positive mental health is at the forefront of the minds of commissioners, health care providers, and the general public alike, this service evaluation demonstrates the positive effect that carefully planned dental bleaching can have on the mental wellbeing of under 18-year-olds with discoloured teeth.